Stereoselective one-step construction of vicinal quaternary and tertiary stereocenters of the 5,10b-ethanophenanthridine skeleton: total synthesis of (+/-)-maritidine - Pandey, Ganesh; Gupta, Nishant R.; Pimpalpalle, Tukaram M. (Organic Letters, 2009)
The challenging vicinal quaternary and tertiary stereocenters of the 5,10b-ethanophenanthridine skeleton are created in a single step utilizing intramolecular [3 + 2]-cycloaddition of nonstabilized azomethine ylide as the key step. The application of the chemistry is demonstrated by synthesizing (+/-)-maritidine.